Living with risk in drylands: Archaeological perspectives. (December 2022) - Barker, Graeme
This paper reflects on the themes illustrated in the 11 case studies on the archaeology of drylands. The papers emphasise the diversity of dryland forms, and of the landscapes within them, the implications of this diversity for the societies living in them, and the need to integrate palaeoenvironmental and archaeological approaches in their study. These studies recognise that how past dryland societies recognised risks and opportunities in drylands, including at times of ecological change (whether climatic and/or anthropogenic) may have been very different from our own notions of post-Enlightenment rationality. They provide examples of very different responses to aridification including: abandoning places and lifeways; specialising in alternative rhythms of life and resources; diversifying and broadening the subsistence base to spread risk; and applying new technological and social solutions to make drylands easier to live in. Whilst emphasising the challenges in both theoretical frameworks and methodologies if we are to better understand the interplay between ecological and social drivers of dryland histories, importantly they demonstrates the capacity of dryland peoples to take both wise and foolish decisions in relation to their own survival and to the sustainability of the natural resource, often with implications for their neighbours. These are lessons that resonate with the pressures on drylands and dryland peoples today.